"We are not getting jobs": Job seeking Problems of People with Disability and Coping Strategies adopted in an Urban Traditional Community in Ghana. - Enoch, Acheampong; Edusei, Anthony Kwaku; Paul, Okyere; Mensah, Akohene Kofi; Adjei, Rose Odotei; Appiah-Brempong, Emmanuel (Disability, CBR & Inclusive Development)
Purpose: The study aimed to examine how misconceptions affect the ability of people with disability to find and maintain jobs, and the coping strategies they adopt to manage their economic conditions. Methods: A qualitative study was conducted with special focus on the Kumasi Metro. Purposive sampling enabled the researchers to select participants on the basis of their own set of inclusion criteria. Data was collected through Focus group discussions and interviews that were conducted in the local language, Twi. The raw data was transcribed from Twi to English, using the notes taken during the discussions and comparing it with information recorded on tapes and audio recorders. Corrected and transcribed data was grouped under the various themes of the discussions. Data was analysed through the question-led approach. The most identified themes have been presented as the major findings with related headings. Some responses have been quoted to support the findings. Results: People with disability who participated in the study experienced unemployment, job-seeking problems, the desire to maintain jobs, inability to retain jobs as a result of negative attitudes from co-workers and members of the larger community, and faced difficulty in paying personal bills. To manage their problems, the tendency was to avoid and withdraw from normal societal interaction, and while some begged for alms on the street, others relied on government policies and financial interventions. Conclusion and Implications: It is recommended that stakeholders should intensify public education on disability. Public education should be custommade to suit the community's needs and understanding of the condition, taking into account local culture and belief systems. People with disability should be encouraged to form groups for self-help programmes, especially at the community level.